Experimental study on forced convection heat transfer from plate-fin heat sinks with partial heating - Lee, Jae Jun; Kim, Hyun Jung; Kim, Dong Kwon (Processes, 2019)
In this study, plate-fin heat sinks with partial heating under forced convection were experimentally investigated. The base temperature profiles of the plate-fin heat sinks were measured for various heating lengths, heating positions, flow rates, and channel widths. From the experimental data, the effects of heating length, heating position, and flow rate on the base temperature profile and the thermal performance were investigated. Finally, the characteristics of the optimal heating position were investigated. As a result, it was shown that the optimal heating position was on the upstream side in the case of the heat sinks under laminar developing flow, as opposed to the heat sinks under turbulent flow. It was also shown that the optimal heating position could change significantly due to heat losses through the front and back of the heat sink, while the effects of the heat loss through the sides of the heat sink on the optimal heating position were negligible. In addition, it was shown that the one-dimensional numerical model with empirical coefficients could predict the important trends in the measured temperature profiles, thermal resistances, and optimal heating lengths.
Keywords: Forced convection; Partial heating; Plate-fin heat sink